2011
DOI: 10.1007/s10439-011-0458-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Modeling-based Left Ventricular Diastatic (Passive) Chamber Stiffness Determination with In-Vivo Validation

Abstract: The slope of the diastatic pressure-volume relationship (D-PVR) defines passive left ventricular (LV) stiffness κ. Although κ is a relative measure, cardiac catheterization, which is an absolute measurement method, is used to obtain the former. Echocardiography, including transmitral flow velocity (Doppler E-wave) analysis, is the preferred quantitative diastolic function (DF) assessment method. However, E-wave analysis can provide only relative, rather than absolute pressure information. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…The lack of correlation of the deceleration time with passive PV curve parameters observed in our study is probably related to its sensitivity to relaxation (32). Operating stiffness during diastasis can also be accurately determined by fitting the transmitral flow spectrogram to a kinematic mathematical model (19). Despite the fact that LV relaxation is still frequently not completed during this phase (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The lack of correlation of the deceleration time with passive PV curve parameters observed in our study is probably related to its sensitivity to relaxation (32). Operating stiffness during diastasis can also be accurately determined by fitting the transmitral flow spectrogram to a kinematic mathematical model (19). Despite the fact that LV relaxation is still frequently not completed during this phase (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, our method has an additional advantage over these previous single-beat approximations. Because the algorithm processes data from multiple beats in an integral fashion, the spontaneous variations in load caused by breathing (19) can be incorporated in future developments. For these reasons, we believe that global optimization is the most accurate method available to date to characterize diastolic properties in vivo without the need of occluding the vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…43 In contrast, the PDF approach accurately predicts elevated ventricular filling pressures in patients with normal ejection fraction and diastolic dysfunction. 21–23 This technique is causality based (on the suction pump attribute of the left ventricle), and is unique in its ability to quantify diastolic function in terms of relaxation, stiffness, and load as determinants of transmitral flow.…”
Section: Discussionmentioning
confidence: 99%
“…39 Beat-to-beat variation in diastatic volume and pressure generates a locus of P, V points whose slope via linear regression defines in vivo passive chamber stiffness, 39 easily determined directly from E-wave analysis. 40 Although pioneering work indicated that DT and stiffness 16 are inversely related, subsequent PDF analysis has refined that view by showing that E-wave DT is determined jointly by stiffness and relaxation (k and c PDF Figure 3. E-waves of 2 selected subjects (normal pattern, pseudonormal pattern) with indistinguishable E-wave duration, E peak , E/A ratio but significantly different values for PDF parameters (k and c) and stiffness and relaxation components of DT (DT s and DT r ).…”
Section: Pdf Analysis Of E-waves Diastolic Function and Dt Fractionmentioning
confidence: 99%